Clearing, settlement, and custody - Loader, David (Operations management series (Securities Institute))
Clearing, Settlement and Custody' focuses on the clearing, settlement and custody functions by analyzing how they work and the interaction between the organizations involved. The author examines the roles of clearing houses, central counterparties, central securities depositories and the custodians, as well as, assessing the impact on the workflow and procedures in the operations function at banks, brokers and institutions. The changes that are taking place in the industry are explored and the impact for operations managers and supervisors assessed. Clearing, settlement and custody is at the h.